CORRELATION ANALYSIS OF CIRCADIAN RHYTHM WITH SEVERITY OF PSORIASIS AND OBESITY - Yemchenko, Y.O.; Kaydashev, I.P.; Ishcheykin, K.Ye.; Bezeha, O.V.; Vasylyeva, K.V.; Oliinichenko, Ya.O.; Morokhovets, H.Yu. (World of Medicine and Biology, 2023)
The recent increase in cases of comorbidity of psoriasis and obesity leads to severe, atypical, disabling, and therapy-resistant forms of dermatosis, significantly worsen the quality of life of patients, reduces work capacity and social activity of patients, which determines not only the medical but also the social significance of the problem. There is a theoretical rationale for the possible role of circadian rhythm disturbances, manifested by a change in eating behavior, a decrease in sleep duration, and the individual chronotype of patients in developing obesity and some autoimmune diseases. However, this issue remains insufficiently studied and proven. The purpose of our study was to identify the correlation between the circadian rhythm and indicators of changes in the chronotype of a person's working capacity and indicators of the severity of the course of psoriatic disease, the degree of obesity, and the degree of the negative impact of the disease on the quality of life of patients. The results of the correlation analysis showed a very high negative correlation between the chronotype of patients' working capacity and BMI indicators and a high negative correlation between the indicators of the PASI index, ACTIVITY, and the chronotype of patients' working capacity.
Keywords: psoriasis; alimentary obesity; сhronotype; quality of life